Challenges and Opportunities for the Digital Enhancement of Religious Cultural Heritage: A Proposal for the Arca di San Domenico in Bologna - Macaluso, Melissa (Mimesis Journal, 2024)
The article focuses on the enhancement of religious cultural heritage in its original context, taking the Arca di San Domenico as a case study. Moreover, it offers a hypothesis identifying the digital as the most suitable tool for the enhancement of the artwork. Specifically, digital enhancement has been implemented as a Web site prototype, L’Arca di San Domenico Digital, which seeks to promote the work online, as well as being useful during the on-site visit. If used properly, the digital can guarantee effective mediation of the historical-artistic contents without impacting the spiritual function of the shrine by excessively musealizing its chapel.